Odpowiedź :
a) 3x-5y+1=3*5-5*3+1=15-15+1=1
b) x² - y³ + 1=5²-3³=25-27+1=-1
c)2x³-3y²-1=2*2³-3*4²-1=2*8-3*16-1=16-48-1=-33
b) x² - y³ + 1=5²-3³=25-27+1=-1
c)2x³-3y²-1=2*2³-3*4²-1=2*8-3*16-1=16-48-1=-33
a) 3x - 5y + 1 dla x=5 y=3
15 - 15 +1= 1
b)x² - y³ + 1 dla x=(-2) y=(-3)
4 +27 + 1= 32
c)2x³ - 3y² - 1 dla x=2 y=4
2razy8 - 3razy16 - 1= 16-48-1=-49+16=-33
15 - 15 +1= 1
b)x² - y³ + 1 dla x=(-2) y=(-3)
4 +27 + 1= 32
c)2x³ - 3y² - 1 dla x=2 y=4
2razy8 - 3razy16 - 1= 16-48-1=-49+16=-33
a) 3x-5y+1=3*5-5*3+1=15-15+1=1
b) x² - y³ + 1=5²-3³=25-27+1=-1
c)2x³-3y²-1=2*2³-3*4²-1=2*8-3*16-1=16-48-1=-33
b) x² - y³ + 1=5²-3³=25-27+1=-1
c)2x³-3y²-1=2*2³-3*4²-1=2*8-3*16-1=16-48-1=-33